Penggunaan Media Modifikasi Bola Plastik Berisi Pasir Untuk Meningkatkan Hasil Belajar Tolak Peluru Penjaskes Siswa Kelas X MIPA 3 SMA Negeri 2 Watampone - mardiana mardiana (Universitas Negeri Makassar, 2020)
This study aims to determine the increase in learning outcomes Reject bullet Physical Education Sports and Health through the use of plastic ball modification media filled with sand in class X MIPA 3 students of SMA Negeri 2 Watampone Bone Kabupten Bone. The subject of this research is Class X MIPA 3 of SMA Negeri 2 Watampone, Kabupaten Bone with 35 students. The action is carried out in two cycles, the collected data is then processed using quantitative and qualitative descriptive statistical analysis. Qualitatively the percentage of grade X MIPA 3 students in SMA Negeri 2 Watampone Bone District was actively involved in the learning process, increasing in all students of grade X MIPA 3 in SMA Negeri 2 Watampone Kabupaten Bone. From the results of the above analysis, it can be concluded that using modified media of plastic balls containing sand can increase the activity of the process and learning outcomes of shot putting in class X MIPA 3 SMA Negeri 2 Watampone Kabupaten Bone both quantitatively and qualitatively.